QoS Strategies for Wireless Multimedia Sensor Networks in the Context of IoT at the MAC Layer, Application Layer, and Cross-Layer Algorithms - Muwonge Ssajjabbi Bernard; Tingrui Pei; Kimbugwe Nasser (Journal of Computer Networks and Communications)
Wireless multimedia sensor networks (WMSNs) have got capacity to collect both scalar sensor data and multidimensional sensor data. It is the basis for the Internet of things (IoT). Quality of service (QoS) pointers like energy efficiency, reliability, bit error rate, and latency can be helpful in data collection estimation over a network. In this paper, we review a number of QoS strategies for WMSNs and wireless sensor networks (WSNs) in the IoT context from the perspective of the MAC and application layers as well as the cross-layer paradigm. Considering the MAC layer, since it is responsible for regulating the admittance to the shared medium and transmission reliability and efficiency through error correction in wireless transmissions, and for performance of framing, addressing, and flow control, the MAC protocol design greatly affects energy efficiency. We thus review a number of protocols here including contention-free and contention-based protocols as well as the hybrid of these. This paper also surveys a number of state-of-the-art machine-to-machine, publish/subscribe, and request/response protocols at the application layer. Cross-layer QoS strategies are very vital when it comes to system optimization. Many cross-layer strategies have been reviewed. For these QoS strategies, the challenges and opportunities are reviewed at each of the layers considered. Lastly, the future research directions for QoS strategies are discussed for research and application before concluding this paper.